2017
DOI: 10.1152/jn.00521.2017
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of spiking activity in the primary auditory cortex to detection in noise

Abstract: A fundamental problem in hearing is detecting a "target" stimulus (e.g., a friend's voice) that is presented with a noisy background (e.g., the din of a crowded restaurant). Despite its importance to hearing, a relationship between spiking activity and behavioral performance during such a "detection-in-noise" task has yet to be fully elucidated. In this study, we recorded spiking activity in primary auditory cortex (A1) while rhesus monkeys detected a target stimulus that was presented with a noise background.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 117 publications
11
45
0
Order By: Relevance
“…A1 was further defined by its frequency-response properties (see section Auditory paradigms and stimuli) (Recanzone et al, 2000; Rauschecker and Tian, 2004; Kajikawa et al, 2005, 2011; Kusmierek and Rauschecker, 2009; Christison-Lagay et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…A1 was further defined by its frequency-response properties (see section Auditory paradigms and stimuli) (Recanzone et al, 2000; Rauschecker and Tian, 2004; Kajikawa et al, 2005, 2011; Kusmierek and Rauschecker, 2009; Christison-Lagay et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…In primates, population measures of neural function provide a better account of auditory processing in noise than individual units (Christison-Lagay, Bennur et al 2017). We therefore turned to a population decoding approach to examine the effects of noise on representations of vowel identity.…”
Section: Population Decoding Offers a Mechanism For Effects Of Coolingmentioning
confidence: 99%
“…Although many studies report invariance to noise, the improvements in stimulus representations observed in the brain are relatively small compared to large impairments in neural encoding of sounds with decreasing signal-to-noise ratio (SNR). In adverse listening conditions with low SNRs, both neural representation of target sounds and behavioral performance break down (Narayan, Best et al 2007, Schneider and Woolley 2013, Teschner, Seybold et al 2016, Christison-Lagay, Bennur et al 2017 suggesting that degradation in cortical representations may underlie difficulties hearing in noise.…”
Section: Introductionmentioning
confidence: 99%
“…How and where task relevant sensory information is transformed into a decision in the brain is still largely unclear. There have been mixed reports of activity correlated to the reported decision in AC (Christison-Lagay et al 2017;Niwa et al 2012b;Tsunada et al 2016;Tsunada and Cohen 2014). This choice-related activity has been reported in some studies as early as primary auditory cortex (A1) (Christison-Lagay et al 2017;Niwa et al 2012b), with an increasingly larger proportion of neurons showing activity correlated to the decision as one progresses further along the auditory hierarchy to middle lateral (ML) and anterolateral (AL) belt areas (Niwa et al 2013;Tsunada et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There have been mixed reports of activity correlated to the reported decision in AC (Christison-Lagay et al 2017;Niwa et al 2012b;Tsunada et al 2016;Tsunada and Cohen 2014). This choice-related activity has been reported in some studies as early as primary auditory cortex (A1) (Christison-Lagay et al 2017;Niwa et al 2012b), with an increasingly larger proportion of neurons showing activity correlated to the decision as one progresses further along the auditory hierarchy to middle lateral (ML) and anterolateral (AL) belt areas (Niwa et al 2013;Tsunada et al 2016). This suggests that sensory evidence becomes increasingly transformed to inform a task-relevant decision as the information is passed along the processing stream (Bizley and Cohen 2013;Hackett 2011;Romanski et al 1999).…”
Section: Introductionmentioning
confidence: 99%